Energy Deficiency in Soldiers: The Risk of the Athlete Triad and Relative Energy Deficiency in Sport Syndromes in the Military - O'Leary, Thomas J.; Wardle, Sophie L.; Greeves, Julie P. (Frontiers in Nutrition, 2020)
Military personnel experience energy deficit (total energy expenditure higher than energy intake), particularly during combat training and field exercises where exercising energy expenditures are high and energy intake is reduced. Low energy availability (energy intake minus exercising energy expenditure expressed relative to fat free mass) impairs endocrine function and bone health, as recognised in female athletes as the Female Athlete Triad syndrome. More recently, the Relative Energy Deficiency in Sport (RED-S) syndrome encompasses broader health outcomes, physical and cognitive performance, non-athletes, and men. This review summarises the evidence for the effect of low energy availability and energy deficiency in military training and operations on health and performance outcomes. Energy availability is difficult to measure in free-living individuals but doubly labelled water studies demonstrate high total energy expenditures during military training; studies that have concurrently measured energy intake, or measured body composition changes with DXA, suggest severe and/or prolonged energy deficits. Military training in energy deficit disturbs endocrine and metabolic function, menstrual function, bone health, immune function, gastrointestinal health, iron status, mood, and physical and cognitive performance. There are more data for men than women, and little evidence on the chronic effects of repeated exposures to energy deficit. Military training impairs indices of health and performance, indicative of the Triad and RED-S, but the multi-stressor environment makes it difficult to isolate the independent effects of energy deficiency. Studies supplementing with energy to attenuate the energy deficit suggest an independent effect of energy deficiency in the disturbances to metabolic, endocrine and immune function, and physical performance, but randomised controlled trials are lacking.